Representing ideas by animated digital models in architectural competitions - Spallone, Roberta; Lo Turco, Massimiliano; Sanna, Marco (ARCC Conference Repository, 2018)
This paper presents the results of the research and of related didactic activity, about digital representation in contemporary architectural competitions. 3D digital models, and more recently requested animations, represent a powerful tool for increasing evaluation capability by jury members as well as knowledge and comprehension by common people. The high complexity in creating and animating 3D digital models has to face an unusual separation of jobs and responsibilities between atelier activities and rendering works. The research constitutes one topic of a teaching, given in the 1st degree of Architecture Sciences (Polytechnic of Turin -Italy) and involves also continuous updating about software potentialities. Aim of the didactic activity is to provide the students some critical and operative tools in order to give them the whole mastery of synthetic representation of their design ideas. We can foresee, in future architectural competitions, the implementation of 4D representation, also referring to its progresses and applications to other media, like cinema and entertainment.